THE IMPACT OF RUMORS ON THE PRICES OF THE MOST TRADED STOCKS ON THE BRAZILIAN STOCK EXCHANGE (B3) - Lima, Heitor Vinicius Costa; da Cruz, Fábio Marques (Editora Impacto Científico, 2025)
This article analyzes the role of information and the dissemination of rumors in the price dynamics of the Brazilian stock market, focusing on the relationship between financial rumors, official announcements, and fluctuations in asset prices. The study is based on an empirical approach applied to stocks listed on B3, selected according to the highest financial trading volume in the period from 2019 to 2023, including PETR4, VALE3, ITUB4, BBDC4, and MGLU3. The research uses historical price series adjusted for corporate events, such as stock splits, as well as records of rumors and official communications released to the market. The theoretical framework discusses concepts related to market efficiency, information asymmetry, and the role of corporate communication in price formation. Methodologically, computational tools are employed for data collection, processing, and integration, as well as descriptive statistical techniques and outlier identification for return analysis. The results indicate that financial rumors are associated with atypical variations in stock prices, especially when they precede official announcements, revealing stronger reactions to rumors of a negative nature. It is concluded that unofficial information exerts a relevant influence on market behavior, reinforcing the importance of informational transparency, regulatory oversight, and critical analysis by investors. DOI: https://doi.org/10.56238/edimpacto2025.065-006